2010
DOI: 10.1080/15287390903578539
|View full text |Cite
|
Sign up to set email alerts
|

Muramic Acid, Endotoxin, 3-Hydroxy Fatty Acids, and Ergosterol Content Explain Monocyte and Epithelial Cell Inflammatory Responses to Agricultural Dusts

Abstract: In agricultural and other environments, inhalation of airborne microorganisms is linked to respiratory disease development. Bacterial endotoxins, peptidoglycans, and fungi are potential causative agents, but relative microbial characterization and inflammatory comparisons amongst agricultural dusts are not well described. The aim of this study was to determine the distribution of microbial endotoxin, 3-hydroxy fatty acids (3-OHFA), muramic acid, and ergosterol and evaluate inflammatory responses in human monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
144
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(150 citation statements)
references
References 47 publications
6
144
0
Order By: Relevance
“…Dust from large animal farming is a complex mixture, and factors other than endotoxin and glucan, such as muramic acid and 3-hydroxy fatty acid, may contribute to respiratory inflammation and these components should therefore be added to the list of markers (Poole et al, 2010). Regarding the horses being examined, for most management systems in our northern climates stabled horses spend far more time indoors than their keepers on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
“…Dust from large animal farming is a complex mixture, and factors other than endotoxin and glucan, such as muramic acid and 3-hydroxy fatty acid, may contribute to respiratory inflammation and these components should therefore be added to the list of markers (Poole et al, 2010). Regarding the horses being examined, for most management systems in our northern climates stabled horses spend far more time indoors than their keepers on a daily basis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated inflammatory responses have also been found in humans working in agricultural settings (May et al, 2012;Poole et al, 2010).…”
Section: Potential Health Effects Of Bioaerosols From Composting Facimentioning
confidence: 99%
“…There were no studies identified that would enable the estimation of incidence rates of occupational allergic disease, one of the most frequent occupational respiratory disorders. However, respiratory and allergic disease following elevated exposures to some bioaerosols, such as endotoxin and Aspergillus fumigatus (Rautiala et al, 2003), was noted in other occupations including agricultural workers (May et al, 2012;Poole et al, 2010) and domestic waste collectors that were not considered in this review. The lack of longitudinal studies is most likely due to the practical difficulties of longitudinal studies in these settings, and the difficulty in obtaining historical data due to the relatively recent development of the composting industry.…”
Section: Health Studiesmentioning
confidence: 99%
“…Farming is also a known occupational hazard for developing musculoskeletal diseases such as osteoarthritis (OA) and rheumatoid arthritis (RA) (8)(9)(10)(11)(12). The organic dust exposure is complex, involving a wide diversity of microbial motifs (e.g., peptidoglycans [PGNs] and endotoxin) and particulate matter, which elicit airway inflammatory responses in mice (7,13). Namely, repetitive organic dust exposures induce the development of lymphoid aggregates and peribronchiolar/ vascular inflammation, comprised of T and B lymphocytes and macrophages with associated neutrophil recruitment (5,14,15).…”
mentioning
confidence: 99%